The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1055/s-0034-1393309
|View full text |Cite
|
Sign up to set email alerts
|

Nicht-invasive Beatmung als Therapie der akuten respiratorischen Insuffizienz

Abstract: The non-invasive ventilation (NIV) is widespread in the clinical medicine and has attained meanwhile a high value in the clinical daily routine. The application of NIV reduces the length of ICU stay and hospitalization as well as mortality of patients with hypercapnic acute respiratory failure. Patients with acute respiratory failure in context of a cardiopulmonary edema should be treated in addition to necessary cardiological interventions with continuous positive airway pressure (CPAP) or NIV. In case of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
55

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 113 publications
3
21
0
55
Order By: Relevance
“…The numbers needed to treat to reduce mortality was only 8. At present, NIV is a standard of care in COPD patients with acute respiratory failure [3,38,44].…”
Section: Noninvasive Ventilationmentioning
confidence: 99%
“…The numbers needed to treat to reduce mortality was only 8. At present, NIV is a standard of care in COPD patients with acute respiratory failure [3,38,44].…”
Section: Noninvasive Ventilationmentioning
confidence: 99%
“…Studies from 2001 that included selected immunosuppressed patients with pneumonitis and ARF showed that early initiation of NIV was associated with significant reductions in the rates of endotracheal intubation and serious complications with improved likelihood of survival to hospital discharge [92]. The 2015 published guidelines of the German Society of Pneumology and Ventilatory Medicine recommend a NIV trial in immunosuppressed (hemato-oncological) patients to avoid intubation [93]. In view of this recommendation, however, it is important to point out contraindications and criteria for NIV termination as well as intubation criteria.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Even NIV application is to be limited only to mild forms of ARDS, as its use is associated with higher rates of treatment failure and mortality in severe forms [12].…”
Section: Discussionmentioning
confidence: 99%